2016
DOI: 10.1002/aenm.201502195
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Electrode‐Induced Losses in Organic Solar Cells by Tailoring a Quasi‐Ohmic Contact to Fullerenes via Solution‐Processed Alkali Hydroxide Layers

Abstract: It is shown that the performance of inverted organic solar cells can be significantly improved by facilitating the formation of a quasi‐ohmic contact via solution‐processed alkali hydroxide (AOH) interlayers on top of n‐type metal oxide (aluminum zinc oxide, AZO, and zinc oxide, ZnO) layers. AOHs significantly reduce the work function of metal oxides, and are further proven to effectively passivate defect states in these metal oxides. The interfacial energetics of these electron collecting contacts with a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…To our knowledge, the reduction of the WF with alkali carbonates–modified SnO 2 might originate from the formation of an interface dipole between the alkali atoms and the metal oxides (M–O–A) in SnO 2 /alkali carbonate samples, where M, O, and A stand for metal, oxygen, and alkali metal species, respectively. 23…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the reduction of the WF with alkali carbonates–modified SnO 2 might originate from the formation of an interface dipole between the alkali atoms and the metal oxides (M–O–A) in SnO 2 /alkali carbonate samples, where M, O, and A stand for metal, oxygen, and alkali metal species, respectively. 23…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this might originate from the increased dipole moments at the interface between the active layers and the ETLs because of the increasing electronegativity of the alkali metals, from Li to Rb. 23 It has been reported that the counter anions of electron-transport materials showed different behaviors in OSCs. 64,65 Because these alkali carbonates possess different metal ions, especially the sizes of these metal ions are different, the different behaviors in our iOSCs are expected.…”
Section: Resultsmentioning
confidence: 99%
“…However, the quality of solution-based ZnO film suffers from the surface defects or dangling bonds, which may act as charge trap sites or recombination centers [ 21 23 ]. To solve the above-mentioned problems, several strategies such as surface passivation or doping were reported to control the interfacial properties of heterojunction [ 24 28 ]. All of them have made promising progresses in the improvement of interface quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the original development of ETLs, a number of n‐type metal oxides (e.g., ZnO, TiO 2 , and CsCO 3 ) have been used as cathode interlayers to replace the low work‐function metals (e.g., Ca, Ba, and Mg) in the standard device geometry of PSCs for alleviating the air‐sensitive problem associated with such cathodes . However, these n‐type metal oxides could have poor interfacial contact with the organic active layer, which will reduce the electron extraction and increase the series resistance ( R S ) . Thus, in the last few years, finding solution‐processed organic interlayers become an important topic in the field of OSCs.…”
Section: Introductionmentioning
confidence: 99%